Risk of lingual nerve injuries in removal of mandibular third molars: a retrospective case-control study - Itaru Tojyo; Takashi Nakanishi; Yukari Shintani; Kenjiro Okamoto; Yukihiro Hiraishi; Shigeyuki Fujita (SpringerOpen, 2019)
Abstract Background Through the analysis of clinical data, we attempted to investigate the etiology and determine the risk of severe iatrogenic lingual nerve injuries in the removal of the mandibular third molar. Methods A retrospective chart review was performed for patients who had undergone microsurgical repair of lingual nerve injuries. The following data were collected and analyzed: patient sex, age, nerve injury side, type of impaction (Winter's classification, Pell and Gregory's classification). Ratios for the respective lingual nerve injury group data were compared with the ratios of the respective data for the control group, which consisted of data collected from the literature. The data for the control group included previous patients that encountered various complications during the removal of the mandibular third molar. Results The lingual nerve injury group consisted of 24 males and 58 females. The rate of female patients with iatrogenic lingual nerve injuries was significantly higher than the control groups. Ages ranged from 15 to 67 years, with a mean age of 36.5 years old. Lingual nerve injury was significantly higher in the patient versus the control groups in age. The lingual nerve injury was on the right side in 46 and on the left side in 36 patients. There was no significant difference for the injury side. The distoangular and horizontal ratios were the highest in our lingual nerve injury group. The distoangular impaction rate in our lingual nerve injury group was significantly higher than the rate for the control groups. Conclusion Distoangular impaction of the mandibular third molar in female patients in their 30s, 40s, and 50s may be a higher risk factor of severe lingual nerve injury in the removal of mandibular third molars.